Unveiling contextual influences of maternal satisfaction with labour care services in Nigeria: A qualitative inquiry - Awotunde, T.A; Ani-Amponsah, M.; Ajala, D.E.; et al. (African Journal of Primary Health Care & Family Medicine, 2024)
Background: In light of the rising global effort to lower maternal mortality rates, it is crucial for low- and middle-income countries with poor maternal indices to investigate the problem of maternal satisfaction and the key elements that affect it. To this effect, this study explored the experiences of postnatal women in relation to labour services and investigated the factors that contribute to their overall satisfaction. Aim: The study set out to explore factors influencing maternal satisfaction with labour care services in Ogbomoso, Oyo State, Nigeria. This study ultimately seeks to advance our understanding of this phenomenon to impact labour care and policy. Setting: The study was conducted among multiparous women who had their antenatal care and delivery in Ogbomoso, Oyo State, Nigeria. Methods: A qualitative study was performed using in-depth interviews among postnatal women. Results: The results revealed a number of variables that could affect the women’s satisfaction with labour care, including the choice of health facility, healthcare providers, environment of the facility, assurance of privacy, treating patients with dignity, provision of needed amenities and having a well-planned postnatal care assessment. Conclusion: The study revealed that the costs of care, the skill of the caregiver, the provision of confidential and dignified care, and the availability of supplies all have an impact on maternal satisfaction. Hospital administration should address these issues to enhance the experience of women and labour care services. Contribution: The study’s findings provide insights that will inform strategies to improve the quality of care being provided to parturients in Nigeria.
Research Article
Keywords: labour; maternal satisfaction; postnatal; labour care services; factors